Financial Sector Assessment : Kuwait - World Bank (Washington, DC, 2013)
A joint International Monetary Fund (IMF)-World Bank financial sector assessment team visited Kuwait in early September 2003, at the request of the government of Kuwait and the central bank. This financial sector assessment report is based on analyses undertaken during that mission. The principal objective of the mission was to assist the authorities in evaluating the strengths, vulnerabilities, and key development opportunities in the financial system. The team sought to identify the measures that should be taken, both to avoid potentially destabilizing conditions and thereby reduce financial sector vulnerabilities, and to improve the foundation for a sound, efficient and deep financial sector that would contribute to economic development, particularly of the non-oil segment of the Kuwaiti economy. The mission also provided an assessment of the observance of international standards and codes in financial regulation and supervision covering three international standards and codes: the base core principles for effective banking supervision; the objectives and principles of securities regulation; and the anti-money laundering and combating the financing of terrorism standards. These standards assessments underpin the analysis and recommendations of this report.